Direct capture of the left bundle branch compared to left bundle branch area pacing deteriorates interventricular synchrony but improves left ventricular lateral wall depolarization duration. (24th May 2021) - Curila, K; Jurak, P; Waldauf, P; Halamek, J; Karch, J; Plesinger, F; Susankova, M; Znojilova, L; Viscor, I; Vondra, V; Smisek, R; Leinveber, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): This paper was supported by the Charles University Research Centre program No. UNCE/MED/002 and 260530/SVV/2020 Background: Direct and indirect pacing of the left bundle branch are novel pacing techniques preserving LV synchrony. Aim of the study was to compare differences in ventricular activation between them using an UHF-ECG. Methods: The left septal lead placement was done in 68 patients with bradycardia. Four distinct ventricular captures were described; nonselective LBBp (nsLBBp), selective LBBp (sLBBp), paraLBBp and left bundle branch area capture (LBBap). The timings of local ventricular activations and local depolarization durations were displayed by the UHF-ECG. e-DYS was calculated as a difference between the first and last activation. Results: There were 35 nsLBBp, 21 paraLBBp, 12 sLBBp and 96 LBBap obtained in 68 patients.  The nsLBBp compared to LBBap caused worse interventricular synchrony (e-DYS -23 ms (-28;-18) vs -12 ms (-17;-8), p < 0.001), but improved LV lateral wall depolarization duration. The sLBBp, nsLBBp and paraLBBp differed in e-DYS; -31 ms (-38;-24) vs -23 ms (-28;-17) vs -13 ms (-20;-7), p < 0.01 between each of them. Their left ventricular depolarization durations were the same, but they were longer when pacing resulted in the left axis deviation. If the direct capture of the LBB was not confirmed (LBBap), LV depolarization duration was deteriorated irrespective of the QSR morphology in the V1 or RWPT in the V5. Examples of UHF-ECG maps during LBBap, paraLBBp and nsLBBp are shown in Figure 1. Conclusions: The direct capture of the left bundle branch deteriorates interventriclar synchrony but improves the depolarization duration of the left ventricular lateral wall compared to left ventricular myocardial septal pacing.